2012
DOI: 10.1002/rra.2633
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the Physical Management of an Invasive Alien Plant for Riparian Plant Species Richness and Diversity

Abstract: Management methods to control or eradicate invasive alien species should be guided by research into their efficacy in relation to the target species as well as their wider effects on the community. Impatiens glandulifera Royle (Balsaminaceae) is an invasive alien species, which has spread rapidly across Europe and North America, particularly colonizing riverbanks, wet woodlands, and wastelands. The effectiveness of two mechanical control measures and their impacts on community plant species richness and divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 37 publications
(55 reference statements)
3
11
1
1
Order By: Relevance
“…glandulifera was in a comparable order of magnitude as the competitive effect of the natives on their conspecifics (intraspecific competition). In contrast to the afore-mentioned field studies [ 16 , 17 ] found a rather negative impact of I . glandulifera on riparian vegetation.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…glandulifera was in a comparable order of magnitude as the competitive effect of the natives on their conspecifics (intraspecific competition). In contrast to the afore-mentioned field studies [ 16 , 17 ] found a rather negative impact of I . glandulifera on riparian vegetation.…”
Section: Discussioncontrasting
confidence: 81%
“…This moderate ranking was justified with the mixed results from field studies on the impact of I . glandulifera on native plant communities [ 11 , 16 19 ]. Thus, a deeper understanding of the interaction between I .…”
Section: Introductionmentioning
confidence: 99%
“…The habitat depending impact of I. glandulifera indicates that the impact gets stronger with increasing cover of I. glandulifera. This is also indicated by Cockel et al (2014). In our study the wet-dark micro-habitat with the lowest cover of I. glandulifera, was the least affected.…”
Section: The Impact Of Impatiens Glandulifera Depended On the Micro-hsupporting
confidence: 74%
“…German and European Union nature conservation authorities emphasize the impact on diversity and threat to other species (European Union 2014, Nehring et al 2015). Taking this study and all available ones into account, the impact of I. glandulifera on plant species diversity can be rated to be relatively low (Hejda and Pyšek 2006, Hejda et al 2009, Diekmann et al 2016, Čuda et al 2017 even if some studies showed stronger effects (Hulme and Bremner 2006, Cockel et al 2014, Kiełtyk and Delimat 2019. Indeed, we found a negative impact on the dominant natives, U. dioica and F. ulmaria, but they are in general very common and widespread in Central Europe and thus not expected to be threatened (Schreiber 1958, Weber 1995.…”
Section: Assessment Of the Invasiveness Of Impatiens Glanduliferamentioning
confidence: 77%
See 1 more Smart Citation